Outcomes of cataract surgery performed by non-physician cataract surgeons in remote North Cameroon. Issue 8 (5th October 2018) - Fortané, Magali; Bensaid, Philippe; Resnikoff, Serge; Seini, Kali; Landreau, Nathalie; Paugam, Jean-Michel; Nagot, Nicolas; Mura, Thibault; Serrand, Chris; Villain, Max; Daien, Vincent
Abstract : Objective: To report the outcomes of cataract surgery performed by non-physician cataract surgeons due to lack of ophthalmologists in remote areas of North Cameroon. Design: Prospective cohort study. Setting: The main centre of the non-governmental organisation Ophtalmo Sans Frontières in Lagdo. Participants and interventions: Age-related cataract surgery performed between 28 November 2016 and 17 May 2017. Main outcomes measures: The main outcome measure was presenting visual acuity (PVA) 1–4 weeks after surgery, classified according to the WHO as good (PVA ≥6/18), borderline (PVA 6/60–6/18) and poor (PVA <6/60). The WHO definition of blindness (visual acuity <3/60) and severe visual acuity (visual acuity 3/60–6/60) was used to assess the proportion of patients with a change in WHO category. Results: We included 474 eyes of 474 patients; the mean (SD) age was 63.9 (15) years (42.2% female). At 1–4 weeks after surgery, the surgical outcome was good for 170 patients (41.1%), borderline for 213 (51.5%) and poor for 31 (7.5%). In all, 224 patients (47.2%) had blindness or severe visual impairment before cataract surgery and 22 (5.3%) at 1–4 weeks after surgery. Poor visual outcome was associated with older age (p=0.018), preoperative blindness or severe impairment (p=0.012) and surgical complications (p=0.019). Conclusion: Blindness and severe visual impairment were significantly decreased in the early postoperative period. Poor outcomes were associated with older age, low preoperative binocular visual acuity and intraoperative complications. Non-physician cataract surgeons may compensate for the lack of ophthalmologists in remote areas of low-income and middle-income countries.